An attempt at an algebraic theory of crystal structure - Aboav, David A. (Image analysis and stereology, 2000)
Since, for reasons to be examined in a later instalment of this work, the postulates of Euclid do not seem suited for the purpose, an attempt is made toclassify regularities in the observed diffraction of X-rays by matter in thecrystalline state on a "Pythagorean", or purely numerical basis
Keywords: Crystallography, X-Ray; Kristalografija radiografska; Modeli teoretski; Models, Theoretical; crystallography; kristalografija; kristali; zgradba; algebraična geometrija